Find the Following Sum!

Calculus Level 2

Evaluate

lim N ( 1 2 N + 1 2 N + 1 + 1 2 N + 2 + 1 2 N + 3 + + 1 3 N ) . \lim_{N\to\infty} \left(\frac{1}{2N}+\frac{1}{2N+1}+\frac{1}{2N+2}+\frac{1}{2N+3}+\dots+\frac{1}{3N}\right).

The answer is of the form ln a b , \ln \frac{a}{b}, where a a and b b are coprime positive integers.

Find a + b a+b .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Nick Turtle
Oct 22, 2017

Expressed with sigma notation, the expression is equivalent to lim N i = 0 N 1 2 N + i \displaystyle\lim_{N\to\infty}{\displaystyle\sum_{i=0}^{N}{\frac{1}{2N+i}}} .

An easy way to solve this would be to use integrals. To do that, we first need to manipulate this (the reason should hopefully be clear soon): lim N i = 0 N 1 N 1 2 + i N \displaystyle\lim_{N\to\infty}{\displaystyle\sum_{i=0}^{N}{\frac{1}{N}\frac{1}{2+\frac{i}{N}}}} .

Define x = i N x=\frac{i}{N} . For sigma notation, each increment is by 1 1 . Thus, d x = i + 1 N i N = 1 N dx=\frac{i+1}{N}-\frac{i}{N}=\frac{1}{N} .

In addition, the bounds of the sigma are from i = 0 i=0 to N N . Thus, the bounds for x x , which is defined as x = i N x=\frac{i}{N} , are from x = 0 x=0 to 1 1 .

In integral notation, the original sum is then 0 1 d x 2 + x \displaystyle\int_{0}^{1}\frac{dx}{2+x} .

(If this does not make sense, remember that a b f ( x ) d x = ( b a ) lim N i = 0 N f ( a + ( b a ) i N ) N \displaystyle\int_{a}^{b}f(x)\ dx=(b-a)\displaystyle\lim_{N\to\infty}\displaystyle\sum_{i=0}^{N}\frac{f(a+\frac{(b-a)i}{N})}{N} and work from there.)

Evaluate the integral: 0 1 d x 2 + x = [ ln ( 2 + x ) ] 0 1 = ln ( 3 ) ln ( 2 ) = ln ( 3 2 ) \displaystyle\int_{0}^{1}\frac{dx}{2+x}=[\ln(2+x)]_{0}^{1}=\ln(3)-\ln(2)=\ln(\frac{3}{2}) .

The final answer is thus 3 + 2 = 5 3+2=5 .

Chew-Seong Cheong
Oct 23, 2017

Relevant wiki: Riemann Sums

L = lim N ( 1 2 N + 1 2 N + 1 + 1 2 N + 2 + + 1 3 N ) = lim N k = 0 N 1 2 N + k Dividing up and down by N = lim N k = 0 N 1 N × 1 2 + k N By Riemann sums: lim n 1 n k = a n f ( k n ) = 0 1 f ( x ) d x = 0 1 1 2 + x d x = ln ( 2 + x ) 0 1 = ln 3 2 \begin{aligned} L & = \lim_{N \to \infty} \left(\frac 1{2N} + \frac 1{2N+1} + \frac 1{2N+2} + \cdots + \frac 1{3N}\right) \\ & = \lim_{N \to \infty} \sum_{k=0}^N \frac 1{2N + k} & \small \color{#3D99F6} \text{Dividing up and down by }N \\ & = \lim_{N \to \infty} \sum_{k=0}^N \frac 1N \times \frac 1{2 + \frac kN} & \small \color{#3D99F6} \text{By Riemann sums: } \lim_{n \to \infty} \frac 1n \sum_{k=a}^n f \left( \frac kn \right) = \int_0^1 f(x) \ dx \\ & = \int_0^1 \frac 1{2+x} dx = \ln (2+x) \bigg|_0^1 = \ln \frac 32 \end{aligned}

a + b = 3 + 2 = 5 \implies a + b = 3 + 2 = \boxed{5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...